Synthesis and Biological Activity of Some Aminothiazole Derivatives as Antileishmanial Agents - Rezaei, Zahra; Sarkari, Bahador; Khabnadideh, Soghra; Farjami, Mahbobeh; Mehrjou, Mahsa; Yazdi, Atefeh; Riazimontazer, Elham; Fararouei, Mohammad (Anti-Infective Agents, 2020)
Background: Leishmaniasis is a major health problem which is caused by the protozoan parasite of the genus Leishmania. Cutaneous leishmaniasis is one type of leishmaniasis and selflimited in most of the cases. However, when the lesions come with scars, they make a deep lifelong stigma. Despite being WHO's research priority, the optimum treatment for this disease has not been found yet. The current study aimed to synthesize and assess the activity of some new aminothiazole compounds against Leishmania major-induced cutaneous leishmaniasis in BALB/c mice. Methods: Eight new aminothiazole derivatives were synthesized and their chemical structures were characterized by spectral data 1H-NMR spectroscopy, Mass spectrophotometry and elemental analysis. L. major parasites were inoculated into the tail base of BALB/c mice and the induced lesions were treated every other day with three different doses of the synthesized compounds against meglumine antimoniate as the drug reference for two weeks. Size of the lesions was observed for three weeks and the collected data were analyzed by SPSS software. Also, these compounds are docked into the active site of 14- α-demethylase as the targets in the treatment of leishmaniasis. Results: Among the synthesized aminothiazole derivatives, compounds 1, 2, 3, 4, and 7 had good leishmanicidal effects. Docking binding energies showed that the synthesized compounds could act as inhibitors for 14- α-demethylase. Conclusion: Among the synthesized compounds, compound 3, (N-((4-chlorophenyl)(phenyl) methyl)thiazol-2-amine) was the most promising one which deserves future studies for the treatment of leishmaniasis.
Keywords: 1H-NMR spectroscopy